Pengaruh Resiliensi Baitul Maal Wa Tamwil, Inklusi dan Literasi Keuangan Terhadap Resiliensi Usaha Mikro Selama Covid-19: The Effect of Resilience Baitul Maal Wa Tamwil, Financial Inclusion and Financial Literacy on Micro Enterprise Resilience During Covid-19 - Dzikrina Fikrotus Salma; Eko Ruddy Cahyadi; Budi Purwanto (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Micro business is the sector that has been hit the hardest by the Covid-19 Pandemic. Business capital assistance is the assistance most needed by micro businesses. However, micro enterprises have barriers to access and use of finance. This study aims to analyze the effect of BMT resilience, financial inclusion and financial literacy on the resilience of micro-enterprises during the Covid-19 pandemic with a total of 150 micro-enterprises and 18 BMT respondents in Brebes Regency. Data processing method in the form of quantitative descriptive analysis using SEM-PLS. The results of this study show that the resilience of micro-enterprises during the Covid-19 pandemic was influenced by BMT financial inclusion and financial literacy. BMT makes it easier for micro-enterprises who are unbankable to gain access to financial institutions to obtain business capital and provide basic knowledge about basic financial management so they can survive during a crisis due to a pandemic. On the other hand, BMT as a financial institution requires efforts to remain resilient in the face of the Covid-19 pandemic, among internal and external factors that have a significant effect on BMT resilience are strengthening human resources, capital, management, regulatory compliance, supervision and infrastructure. Keywords: BMT resilience, business resilience, Covid-19 Pandemic, financial inclusion, financial literacy